Gender Equality and the Empowerment of Women and Girls. - OECD (Organization for Economic Cooperation & Development, 2022)
Gender equality and the empowerment of women and girls are prerequisites to the realisation of the 2030 Agenda for Sustainable Development. This Guidance is a practical handbook for development partners supporting those global ambitions.